Safe drinking water for expanding cities - Jinmin, Wang (UNDP, 2013)
The rapid urbanization and industrialization since 1978 have posed some serious environmental challenges for sustainable development in China, with pollution and water shortages ranking among the most pressing issues. Although China is rich in water resources, water availability was only 2,343 cubic metres per capita per annum, which is just a quarter of the global mean. Water resources are unevenly distributed across the country. Floods take place very frequently (Lee, 2006). Before 2000, there was an administrative monopoly on water allocation, with many cities facing severe water shortages. However, with the increasing water shortages, the allocation of water rights solely through administrative means failed to meet the needs of rapid urbanization and economic development in some regions of the country. Yiwu City and Dongyang City became the first Chinese cities to experiment with the partial transfer of water rights in the country in 2000. The partial water-rights transfer agreement between the two cities initiated the reform of the water-resources management system in China.